Structure Design and Kinematic Analysis of New Type of Differential for Automobile Driving Axle - Chen Shuang; He Lianliang (Jixie chuandong)
A new type of designing scheme of spur gear differential used in vehicle drive axle is put forward,its operating principle and characters are analyzed in detail. According to the design project,the design and assemble of axle shaft gear,planet gear,planet carrier and others are created in Pro / E,and imported into ADAMS / View. Then the kinematic simulation and analysis of its two different working conditions of straight driving and handling driving are carried out. The analysis results show that spur gear differential not only can achieve automobile driving axle differential function,but also have advantage of simple construction and easy machining.